2018
DOI: 10.22201/iisue.24486167e.2018.especial.59180
|View full text |Cite
|
Sign up to set email alerts
|

Calidad y evaluación: matrimonio del cielo y el infierno

Abstract: El presente artículo desarrolla dos tesis: 1) a más de 30 años de políticas sobre evaluación educativa, se ha conformado un ecosistema de la evaluación donde los elementos que lo componen se afectan mutuamente, pero sin una lógica coherente; 2) no se ha mostrado que exista relación causal entre la reingeniería del gasto público y la “calidad educativa”; pero los instrumentos de política pública actúan sobre la capacidad de agencia de los actores educativos y crean lógicas diferenciadas de gestión de la evaluac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…For Vera and González-Ledesma (2018), in their article Quality and evaluation: Marriage of heaven and hell, they point out that in the last 40 years, educational evaluation has gone from being a fundamentally diagnostic instrument, which is applied in some countries, to become a practice of global reach, this aspect highlights the importance of the change of vision in the models and practices of evaluation, the authors continue to indicate the need to be considered as a necessary mechanism for the governance of educational systems. It is important to highlight the significant changes experienced in evaluation, from its origins as a diagnostic tool, to expanding its functions as a means to encourage or dissuade behaviors, an aspect that allows us to see the diagnostic and formative function of evaluation.…”
Section: Learning Evaluationmentioning
confidence: 99%
“…For Vera and González-Ledesma (2018), in their article Quality and evaluation: Marriage of heaven and hell, they point out that in the last 40 years, educational evaluation has gone from being a fundamentally diagnostic instrument, which is applied in some countries, to become a practice of global reach, this aspect highlights the importance of the change of vision in the models and practices of evaluation, the authors continue to indicate the need to be considered as a necessary mechanism for the governance of educational systems. It is important to highlight the significant changes experienced in evaluation, from its origins as a diagnostic tool, to expanding its functions as a means to encourage or dissuade behaviors, an aspect that allows us to see the diagnostic and formative function of evaluation.…”
Section: Learning Evaluationmentioning
confidence: 99%
“…Las políticas de modernización y calidad que se impulsaron desde los años noventa descansaron en una lógica de estímulos y recompensas asociados a diversos programas federales y bolsas extraordinarias de financiamiento público, lo que colocó en el centro la combinación contradictoria de procesos de evaluación, cualificación y cuantificación del desempeño universitario (Vera & González-Ledesma, 2018). A lo largo de los años, esa lógica incidió de manera importante en la modificación de la autonomía y en el papel de los gobiernos universitarios en el comportamiento institucional.…”
Section: Autonomía Institucional Y Ciudadanía Académicaunclassified
“…Organizations are therefore more concerned with the well-being of workers (Guest, 2017). One of the most stress-influenced sectors is higher education (Vera & González-Ledesma, 2018). Previous studies revealed that the well-being of educators is less than that of the general public (Education Support Partnership, 2019).…”
Section: Introductionmentioning
confidence: 99%